Complementarity and sequencing of innovations: new varieties and mechanized processing for cassava in West Africa - Johnson, Michael E.; Masters, William A. (Informa UK Limited, 2004)
Complementarity among inter-related innovations may help explain the location and timing of productivity growth, and may be particularly important in the transformation of semi-subsistence agrarian economies. We study the case of cassava in West Africa, where both mechanized processors and new varieties are more widespread in Nigeria than in neighboring countries. One explanation involves complementarity: mechanization may have induced new variety adoption, or vice-versa. We test the magnitude and significance of these linkages using a system of equations approach. Controlling for other factors, we find that new variety adoption consistently increases the likelihood of subsequent mechanization by an average of 75 percent. Mechanization is less consistently associated with subsequent new variety adoption. Historically, mechanization came first – but the later development of new varieties made mechanization much more profitable, and the two then spread together. -- Authors' Abstract